Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.14710/jpu.14.1.81-93
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Perilaku Orang Tua Dalam Melakukan Kekerasan Verbal Terhadap Anak Usia Pra-Sekolah

Abstract: Verbal abuse in children is all forms of greeting parents to children who are threatening, scaring, and insulting. This happens every day at home should be the safest place and refuge for children. Economic, social, employment, lack of knowledge to educate children and parents lack understanding of religion contributing cause parents do violence on their children. Parents commit verbal violence as a way to educate children is naughty and not obedient, so it is necessary to study in order to know the factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 0 publications
1
8
0
25
Order By: Relevance
“…It is arguably due to mature thoughts of older participants which allow them to make their own decisions, so they are less affected by their social environment. Fitriani, Pratiwi, and Susanto (2015) stated that the maturity level of thinking of an individual increase along with his/her age and that their comprehension and mindset will develop. Besides, Khasan (2018) also found that age influenced decision making.…”
Section: Discussionmentioning
confidence: 99%
“…It is arguably due to mature thoughts of older participants which allow them to make their own decisions, so they are less affected by their social environment. Fitriani, Pratiwi, and Susanto (2015) stated that the maturity level of thinking of an individual increase along with his/her age and that their comprehension and mindset will develop. Besides, Khasan (2018) also found that age influenced decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Lingkungan disebutkan sebagai salah satu faktor adanya kekerasan (Fitriana et al, 2015). Individu yang tinggal di lingkungan dimana banyak terjadi kekerasan maka individu tersebut rentan melakukan atau mengalami kekerasan itu sendiri.…”
Section: Hasil Dan Pembahasanunclassified
“…Hal ini berangkat dari pemahaman bahwa setiap orangtua pasti memiliki rasa cinta dan tidak bermaksud melukai anaknya. Orangtua melakukan kekerasan dengan bertujuan anak menjadi disiplin dan berperilaku baik (Fitriana et al, 2015). Sayangnya banyak orangtua yang merasa frustrasi dengan perilaku anak sehingga melakukan kekerasan menjadi pilihan untuk dilakukan.…”
Section: Grafik 3 Penyebab Kekerasan Pada Anakunclassified
“…Berbagai faktor menyebabkan ibu melakukan kekerasan. Salah satunya yaitu cara ibu dalam mengajarkan kedisiplinan terhadap anak dilakukan dengan sikap negatif seperti perlakuan kasar dan hinaan yang merupakan bentuk dari kekerasan (Ekman, 2008 Faktor eksternal yang menyebabkan kekerasan antara lain seperti faktor ekonomi dan faktor lingkungan atau stres sosial serta isolasi sosial (Gelles, 1980;Soetjiningsih, 2002;Fitriana, Pratiwi, & Sutanto, 2015 Temuan penelitian lain memberikan gambaran bahwa ibu menjadi lebih menampilkan perilaku bermusuhan, mengendalikan, dan mengganggu, bahkan dengan bayi (Crittenden, 1985).…”
Section: Berdasarkan Data Dinas Pemberdayaan Perempuan Dan Perlindungunclassified